Impact of the transcription factor IRF8 on limbal epithelial progenitor cells in a mouse model - Kesper, Christiane; Viestenz, Arne; Wiese-Rischke, Cornelia; Scheller, Marina; Hammer, Thomas (Experimental eye research, 2022)
The limbus of the eye is the location of the corneal epithelial stem cell niche. These cells are necessary for continuous renewal of the corneal epithelium. In the case of limbal stem cell deficiency, these cells are damaged, and the whole cornea becomes opaque. It is important to be able to identify stem cells that could be applied for new therapeutic strategies. There are various known markers to characterize these cells, including p63, Nanog, oct4 and FGFR2. However, none of these markers are exclusively expressed in these stem cells (they are also expressed in transient amplified cells). It seems likely that a combination of stem cell markers will be necessary for corneal stem cell identification. The aim of this study was to detect IRF8 in limbal epithelial stem cells and to determine its function. In a mouse model, IRF8 could be detected in limbal and basal epithelial cells of the cornea by histological and immunohistological staining of wild-type mouse eyes. Furthermore, the limbus of the eye was significantly smaller in IRF8-knockout mice than in wild-type mice, and the expression of Nanog was lower in IRF8-knockout mice. This suggests that IRF8 has an influence on the maintenance of stem cell properties in the limbus, possibly by affecting the expression of Nanog. Furthermore, IRF8 has an impact on E-cadherin and N-cadherin expression in the mouse eye.
Gesehen am 11.05.2022